2006
DOI: 10.1037/1099-9809.12.3.578
|View full text |Cite
|
Sign up to set email alerts
|

Cognitions and depressive symptoms among ethnic minority adolescents.

Abstract: Cognitive models have guided effective intervention strategies in the treatment of depression. However, little is known about the cognitive model's relevance in different cultural ethnic groups in the United States. This study examines the cross-sectional and longitudinal associations among cognitive variables and depressive symptoms among African American, Caucasian, and Hispanic adolescents in the United States. Community adolescents (N = 450) ages 14-18 years (African American n = 79; Caucasian n = 273; His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 54 publications
4
33
0
Order By: Relevance
“…For example, Reinemann and Teeter Ellison (2004) found that negative cognitions mediated the relationship between negative life events and depressive symptoms in a sample of urban, ethnic minority middle-school children, the majority of whom were African American. Similarly, Kennard, Stewart, Hughes, Patel, and Emslie (2006) demonstrated that a variety of cognitive variables, (i.e., self-efficacy, negative cognitive errors, and hopelessness) were associated with depressive symptoms in a diverse sample of adolescents. O’Donnell, Moreau, Cardemil, and Pollastri (2010) reported that explanatory style moderated the relationship between interparental conflict and depressive symptoms.…”
mentioning
confidence: 90%
“…For example, Reinemann and Teeter Ellison (2004) found that negative cognitions mediated the relationship between negative life events and depressive symptoms in a sample of urban, ethnic minority middle-school children, the majority of whom were African American. Similarly, Kennard, Stewart, Hughes, Patel, and Emslie (2006) demonstrated that a variety of cognitive variables, (i.e., self-efficacy, negative cognitive errors, and hopelessness) were associated with depressive symptoms in a diverse sample of adolescents. O’Donnell, Moreau, Cardemil, and Pollastri (2010) reported that explanatory style moderated the relationship between interparental conflict and depressive symptoms.…”
mentioning
confidence: 90%
“…We also hypothesized there would be no signifi cant differences in outcomes between the intervention groups. Based on previous research, 15,[17][18][19][20][21][22][23][24][25][26] we also explored whether HIOH patients who had a greater number of depressive symptoms would experience greater improvements in these outcomes at 1 year than would those with fewer depressive symptoms. …”
mentioning
confidence: 99%
“…Kennard et al (2006) reported similar levels of cognitive symptoms in different cultures in community youth. However, the association between cognitions and depressive symptoms were stronger for White than for ethnic minority youth.…”
Section: Patient Variablesmentioning
confidence: 50%